Cultivating the Ethical-Digital Companion: A Socio-Pedagogical Study on Islamic Character Building in the Age of Artificial Intelligence. - Karlina Nina; Septi Gumiandari (Assyfa Journal of Islamic Studies, 2026)
The rapid advancement of artificial intelligence (AI) and digital technology has significantly transformed family dynamics, necessitating a socio-pedagogical shift in Islamic character building (akhlaq) for early adolescents. This study investigates the parental practices, strategies, and socio-pedagogical challenges in digital mediation among parents of seventh-grade students at SMPN 2 Kuningan, Indonesia, aiming to construct a value-based Ethical-Digital Companion model. Utilizing a descriptive qualitative approach, in-depth interviews were conducted with 19 parents. The findings reveal that parents perform five vital socio-pedagogical roles: technology regulators, information filters, educational rule enforcers, digital companions, and role models for digital ethics. The strategies employed include dialogic assistance, proactive regulation, and school-home partnerships, despite persistent challenges such as peer social pressure and parental digital literacy gaps in navigating intelligent technologies. The study concludes that cultivating Islamic character requires a paradigm shift from restrictive technical control to the Ethical-Digital Companion model. This framework contributes to Islamic interdisciplinary studies by synergizing socio-pedagogical strategies with transcendental ethical integrity, ultimately fostering akhlaq resilience in the AI era.